Use of Cyclotron for Radionuclide Production in SPECT Diagnostics at Nuclear Medicine Installation - Nisa, Zakiyatun; Zuhdaniel, Nawal; Hasudungan, Ardiman; Prayogo, Dimas; Rhisma, Wanda; Meireni, Mutia (MUNISI: Military Mathematics and Natural Sciences, 2024)
The development of cyclotron technology in the healthcare industry became important after the production of several radioisotopes with short half-lives were used. Single Photon Emission Computed Tomography (SPECT) became one of the important diagnostic methods, especially in the visualization and functional analysis of internal organs. In Indonesia, cyclotron is only available in a few hospitals and is not fully optimized in the production of radionuclides for SPECT. By involving cyclotron technology in the production of radionuclides for SPECT, it is hoped that this research can make a contribution in advancing the field of nuclear medicine, opening up new opportunities for diagnostic research, and improving the healthcare quality by providing more accurate and timely information to medical practitioners. Relatively low-energy cyclotrons are required to produce PET radionuclides such as 18F, 11C, 13N, 64Cu, and 124I with energies between 2.7 and 5.6 MeV. Medium cyclotrons capable of accelerating protons greater than 10 MeV are required for the production of SPECT radionuclides such as 99mTc, 123I, 201Tl, 111In and 67Ga.